Counseling Issues of Children with ASD Parents - Bagaradnikova E.V (Moscow State University of Psychology and Education, 2018)
Several aspects of the Regional Public Organization for Assistance to Children with Autism Spectrum Disorders "Contact" members work are listed: counseling of parents of children with ASD, informational, psychological and legal support and social security. Well-established experience of consultative work can serve as a basis for the development of parents advisory support technology provided in various organizations, both non-profit and governmental.